Study of tension control systems for automatic rotogravure machines - Rizki Setiadi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
In the manufacturing sector, a large number of machines today use automation technologies. Production will grow and speed up thanks to automation technologies, which includes using rotogravure machines. A machine using a printing technique known as a rotogravure machine is frequently used to print packaging on materials like paper or plastic. No one presently makes fully automatic rotogravure machines in Indonesia. Tension control is one of the automation systems of a rotogravure machine. In this research, tension control, kinds of tension control, and the building of a rotogravure machine tension control system are all topics that will be covered. It uses a descriptive qualitative approach. employing a literature review to gather data and descriptive statistics to analyze it. The study's findings demonstrate that the rotogravure machine is a fast printing device that uses substrates like paper, aluminum, and plastic. The printing procedure begins with the unwinding roll, moves to the infeed, and then continues with the first and second color printing processes, moving as necessary to the outfeed and rewinding roll using a tension control mechanism. The roller-to-roll mechanism used by the machine allows for the tension management because the printed material is subjected to varying strains that must be managed. A rotogravure machine can use four different forms of tension management, specifically speed control for unwinding and rewinding, speed control for unwinding and torque control for rewinding, and speed control for unwinding and rewinding. the creation of a tension control system for a rotogravure machine using the machine's main controller, a PLC and an HMI.